Sustainable aquaculture side-streams derived hybrid biocomposite for bone tissue engineering - Wang, Jun Kit (2022)
Despite being a rich source of bioactive compounds, the current exploitation of aquatic biomass is insufficient. Majority of the aquaculture industry side-streams are currently used for low-value purposes such as animal feed or composting material, with low economical returns. To maximize resource reuse and minimize waste generation, valorization efforts should be augmented with the aim to produce high-value products. Herein, we present a novel aquaculture wastes-derived multi-scale osteoconductive hybrid biocomposite that is composed of chemically crosslinked American bullfrog (Rana catesbeiana) skin-derived type I tropocollagen nanofibrils (~22.3 nm) network and functionalized with micronized (~1.6 μm) single-phase hydroxyapatite (HA) from discarded snakehead (Channa micropeltes) fish scales. The bioengineered construct is biocompatible, highly porous (>90%), and exhibits excellent osteoconductive properties, as indicated by robust adhesion and proliferation of human fetal osteoblastic 1.19 cell line (hFOB 1.19). Furthermore, increased expression level of osteo-related ALPL and BGLAP mRNA transcripts, as well as enhanced osteocalcin immunoreactivity and increasing Alizarin red S staining coverage on the hybrid biocomposite was observed over 21 days of culture. Collectively, the devised "waste-to-resource" platform represents a sustainable waste valorization strategy that is amendable for advanced bone repair and regeneration applications.